Complement regulator-acquiring surface protein 1 of Borrelia burgdorferi binds to human bone morphogenic protein 2, several extracellular matrix proteins, and plasminogen - Hallström, Teresia; Haupt, Katrin; Kraiczy, Peter; Hortschansky, Peter; Wallich, Reinhard; Skerka, Christine; Zipfel, Peter F. (The journal of infectious diseases, 2010)
Lyme disease-causing Borrelia burgdorferi spirochetes express up to 5 complement regulator-acquiring surface proteins (CRASPs). To better define how CRASP-1 contributes to infection, we aimed to identify novel CRASP-1-binding host proteins. Here, we identified a number of novel human CRASP-1-binding proteins, including bone morphogenic protein 2, collagen I, collagen III, collagen IV, fibronectin, laminin, and plasminogen. The plasminogen-binding regions were located in 2 separate regions of CRASP-1. Our results demonstrated that plasminogen-bound CRASP-1 can be converted to plasmin by the urokinase-type plasminogen activator and that proteolytically active plasmin cleaves the synthetic chromogenic substrate S-2251 and the natural substrate fibrinogen. In conclusion, CRASP-1 is a multifunctional protein of B. burgdorferi that binds to several human extracellular matrix proteins and plasminogen. These interactions may contribute to adhesion, bacterial colonization, and organ tropism and may allow dissemination of B. burgdorferi in the host.